Polysaccharide-protein covalent conjugates and their ternary metal complexes - Karahan, Mesut; Mustafaeva, Zeynep; Ozer, Hayrettin (ASIAN JOURNAL OF CHEMISTRY, 2007)
The conjugates based on polysaccharides (polyelectrolyte) and bovine serum albumin (BSA) were studied by high performance liquid chromatography, fluorescence technique. Dextran sulphate(DS)-metal-protein complexes were studied by fluorescence technique and UV-vis absorption spectroscopic analysis. BSA was coupled to polysaccharide by two-methods : by covalent binding of linear macromolecules and by complex formation with metal ions. Aldehyde derivatives of dextran, methyl cellulose and hydroxyethyl cellulose were cross-linked with albumin by covalent bonds. Dextran sulphate (DS) can interact with albumin in the presence of metal ions (M). Various metals (Cu(2+), Zn(2+), Fe(3+), Fe(2+), Ni(2+), Cd(2+), Co(2+) and Mn(2+)) were used for formation of complexes. The character of interactions depends on the composition of [M]/[DS] and [M]/[BSA] ratio, the nature of metals and pH of medium. These studies revealed that in presence of different metal ions DS can form ternary polymer-metal-protein complexes with BSA. Fluorescence quenching by metal ions of tryptophan chromophores of BSA in structure of polycomplexes were used to reveal the structural features of soluble ternary polycomplexes. Two types of bioconjugate particles are formed depending on the method of binding and the conditions of the reaction : at covalent binding of components and at the complex formation via metal ions (Zn(2+), Ni(2+), Cd(2+), Co(2+) and Mn(2+)) the protein molecules in the structure of particles are densely covered by the shell of a polysaccharide coil and practically fenced of from the water environment; at the complex formation via metal ions (Cu(2+), Fe(2+) and Fe(3+)) the ternary polycomplex particles have more friable structures in which protein molecules are practically exposed to the solution.
Keywords: polysaccharides; polyelectrolytes; proteins; covalent conjugates; ternary polycomplexes; BOVINE SERUM-ALBUMIN; AMPHIPHILIC IMMUNOGENS; BETA-LACTOGLOBULIN; DEXTRAN; WATER; Chemistry